B‐cell activating factor detected on both naïve and memory B cells in bullous pemphigoid. Issue 8 (16th July 2014) - Qian, Hua; Kusuhara, Masahiro; Li, Xiaoguang; Tsuruta, Daisuke; Tsuchisaka, Atsunari; Ishii, Norito; Koga, Hiroshi; Hayakawa, Taihei; Ohara, Koji; Karashima, Tadashi; Ohyama, Bungo; Ohata, Chika; et al.
Abstract B‐cell activating factor (BAFF), an important immune regulatory cytokine, is involved in development of autoimmune diseases. Although BAFF is expressed in various cells, including dendritic cells (DCs) and monocytes, BAFF expression on B cells has not been well documented. In the present study, BAFF molecules on DCs and naïve and memory B cells in autoimmune bullous diseases, including pemphigus vulgaris, pemphigus foliaceus and bullous pemphigoid (BP), were analysed by flow cytometry. Compared with healthy controls (HC), BAFF expression on naïve and memory B cells increased significantly in BP. No difference in BAFF receptor expression in naïve and memory B cells was shown among all study groups. Furthermore, BAFF expression in both naïve and memory B cells of BP, but not HC, was detected by confocal microscopic analysis. These results implied that BAFF expressed by B cells may play a pathogenic role in autoimmune bullous diseases, particularly BP.